Conductivity mechanism and dielectric properties of poly (2-aminophenol) with boron nitride and graphite composites - Cogalmis, F. Tuba; Ahlatcyoolu Ozerol, Esma; Okutan, Mustafa; Senkal, B. Filiz (SPRINGER INT PUBL AG, 2021)
Polyaniline (PANI) is one of the important of the conducting polymers because of its easy synthesis, redox recyclability, reversible proton dopability, environmental stability, cost-effectiveness and reasonable electrical conductivity. PANI and its composites have the most promising applications as conducting materials in optoelectronics and microelectronics devices. Recently, PANI composite studies have increased remarkably in order to overcome the negative properties of polyaniline. In this study, 2-Aminophenol as monomer was polymerized oxidatively in the presence of ammonium persulfate as oxidant to obtain poly(2-aminophenol) (P2AMP). Then, 2-Aminophenol was polymerized in the presence of difference weight percentage (1%, 2%, 5%) of Boron nitride and graphite to obtain its composites (P2AMP-BN and P2AMP-GH), respectively. These composites were characterized by using spectroscopic, morphologic and physical methods.
Keywords: 2-Aminophenol; Polyaniline (PANI); Boron nitride (BN); Graphite (GH); Conductive polymer composites; ABSORPTION; DISPERSION; Chemistry